Pengembangan Media Pembelajaran Go Puzzle Pada Mata Pelajaran Pendidikan Pancasila dan Kewarganegaraan untuk Siswa Sekolah Menengah Pertama - Fauziyah, Lia Nurul; Awaliyah, Siti (Universitas Negeri Malang, 2023)
This study aims to develop and test the validity, attractiveness, effectiveness, and applicability of Go Puzzle learning media in the subjects of Pancasila and Civic Education. The procedure used is research and development based on the steps proposed by Borg and Gall. The products produced in this development study are Go Puzzle learning media material for the Formulation and Determination of Pancasila as a State Basis that is valid, interesting, effective, and can be applied in learning. The product validity test is based on the results of material expert validation of 92.78 percent, media expert validation of 91.42 percent, expert validation of learning implementation plans of 95.63 percent, and field learning expert validation of 98.21 percent. The product attractiveness test is based on the results of small group trials of 90.36 percent and the results of large group trials of 93.46 percent. The product effectiveness test is based on the results of large group trials which resulted in an average completeness of students’ scores when pretest was 20.89 percent and post test was 86.89. This shows that there is an increase in the percentage of completeness of scores obtained by students, which is 66 percent. The product applicability test is based on the educator response questionnaire, which is 96.88% which shows that the product developed can be applied in learning. Abstrak: Kajian ini bertujuan untuk mengembangk